2019
DOI: 10.1103/physreve.99.052503
|View full text |Cite
|
Sign up to set email alerts
|

Plectoneme dynamics and statistics in braided polymers

Abstract: Braids composed of two interwoven polymer chains exhibit a "buckling" transition whose origin has been explained through the onset of plectonemic structures. Here we study, by a combination of simulation and analytics, the dynamics of plectoneme formation and their statistics in steady state. The introduction of an order parameter -the plectonemic fraction -allows us to map out the phase boundary between the straight braid phase and the plectonemic one. We then monitor the formation and the growth of plectonem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…As for the obtained value of diffusivity of supercoiling, D σ = 1.6, agrees well with the value obtained by the study of plectoneme dynamics of braided polymers like DNA by Forte et al [49]. In their study, the authors observed that the dynamics of twist is faster than that of writhe, while the obtained decoupled diffusivities were D Tw = 2.0 and D Wr = 0.1, giving the value of diffusivity of supercoiling as a weighted average with contributions of each based on whether the system accommodates a stable plectonemic or straight conformation.…”
Section: Mathematic Model Of Transcriptionally Driven Loop Extrusionsupporting
confidence: 91%
“…As for the obtained value of diffusivity of supercoiling, D σ = 1.6, agrees well with the value obtained by the study of plectoneme dynamics of braided polymers like DNA by Forte et al [49]. In their study, the authors observed that the dynamics of twist is faster than that of writhe, while the obtained decoupled diffusivities were D Tw = 2.0 and D Wr = 0.1, giving the value of diffusivity of supercoiling as a weighted average with contributions of each based on whether the system accommodates a stable plectonemic or straight conformation.…”
Section: Mathematic Model Of Transcriptionally Driven Loop Extrusionsupporting
confidence: 91%
“…This system is known to display a buckling transition at a critical catenation number Ca* which depends on the stretching force f, i.e. Ca* = Ca*( f ) [26][27][28][29][30]. For Ca < Ca*( f ), the braid is straight whereas for Ca > Ca*( f ) the braid buckles and forms plectonemes that resemble those shown by single dsDNA molecules in MT assays [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that polar writhe is not only applicable to the analysis of open curves such as those formed by extended DNA structures but that it can be decomposed into local and nonlocal contributions that can provide additional information about DNA topology that cannot be obtained from the Călugăreanu formalism. In particular, we demonstrate how the non-local component of the polar writhe can be used as a potential indicator of plectoneme formation in both linear and circular DNA structures which we believe will be of particular value to the host of studies performed on effects of plectoneme formation in DNA and braided polymers 54,55 . To aid in the adoption of polar writhe, we have developed a software package, WASP, that can be used to analyze molecular dynamics simulations of DNA.…”
Section: Discussionmentioning
confidence: 84%